Administrative Facilities Competent to Achieve Drug Security - فاضل, مريم صباح; حمزة, وليد مرزة (Journal of Legal Sciences, 2021)
It is known that the economic impact of medicines is not negligible as a pillar of national income because of the profits of its industry contribute to industrial development, and the health impact of medicines can not be underestimated or underestimated, as many people already die in various low-lying countries The middle income because of the difficulty in providing them with safe and effective essential medicines or their inability to buy them to be available to enable them to cure and save their lives.    This requires the development of policies and strategies to save lives by researching the concept of drug security to provide the best possible level of modern health care supported by sound pharmaceutical policies, regional and international agreements, national legislation, technical resources and professional training.    We discuss the importance of the role of the administrative authorities concerned with the investigation and protection of drug security and its necessary endeavor in supporting the national pharmaceutical industries, organizing importation, supervision and control, and following up the supply chain of medicines until they reach the consumer.